Perancangan Sistem Informasi Bimbingan Konseling Berbasis Web Menggunakan Metode Waterfall (Studi Kasus: SMA Negeri Jumapolo) - Candra Kartika; Saprudin (CV. Multi Kreasi Media, 2026)
Supporting kids' intellectual, social, and emotional growth requires guidance and counseling services. These services at SMA Negeri Jumapolo face challenges, particularly with regard to the manual recording of counseling outcomes and the storage of student data. Manual procedures may lead to data loss, delays, and stakeholder access restrictions. This project aims to design and develop a web-based guidance and counseling information system to increase the effectiveness and efficiency of counseling services. The system is developed using the waterfall approach, which includes requirement analysis, system design, implementation, testing, and maintenance, with PHP and MySQL serving as the technical stack. Black box testing ensures that user demands are met by system features. The results demonstrate that counselors may utilizethe system to manage student data and offer counseling services in an orderly and regulated manner.